STING Signaling Drives Production of Innate Cytokines, Generation of CD8+ T Cells and Enhanced Protection Against Trypanosoma cruzi Infection - Vieira, Raquel de Souza; Nascimento, Marilda Savoia; Noronha, Isaú Henrique; Vasconcelos, José Ronnie Carvalho; Benvenuti, Luiz Alberto; Barber, Glen N.; Câmara, Niels Olsen Saraiva; Kalil, Jorge; Cunha-Neto, Edecio; Almeida, Rafael Ribeiro (Frontiers in Immunology, 2022)
A variety of signaling pathways are involved in the induction of innate cytokines and CD8+ T cells, which are major players in protection against acute Trypanosoma cruzi infection. Previous data have demonstrated that a TBK-1/IRF3-dependent signaling pathway promotes IFN-β production in response to Trypanosoma cruzi, but the role for STING, a main interactor of these proteins, remained to be addressed. Here, we demonstrated that STING signaling is required for production of IFN-β, IL-6 and IL-12 in response to Trypanosoma cruzi infection and that STING absence negatively impacts activation of IRF-dependent pathways in response to the parasite. We reported no significant activation of IRF-dependent pathways and cytokine expression in RAW264.7 macrophages in response to heat-killed trypomastigotes. In addition, we showed that STING is essential for T. cruzi DNA-mediated induction of IFN-β, IL-6 and IL-12 gene expression in RAW264.7 macrophages. We demonstrated that STING-knockout mice have significantly higher parasitemia from day 5 through 8 of infection and higher heart parasitism at day 13 after infection. Although we observed similar heart inflammatory infiltrates at day 13 after infection, IFN-β, IL-12, CXCL9, IFN-γ and perforin gene expression were lower in the absence of STING. We also showed an inverse correlation between parasite DNA and the expression of CXCL9, IFN-γ and perforin genes in the hearts of infected animals at day 13 after infection. Finally, we reported that STING signaling is required for splenic IFN-β and IL-6 expression early after infection and that STING deficiency results in lower numbers of splenic parasite-specific IFN-γ and IFN-γ/perforin-producing CD8+ T cells, indicating a pivotal role for STING signaling in immunity to Trypanosoma cruzi.